2010
DOI: 10.21608/jpp.2010.86382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Flood Irrigation and Potassium Fertilization Treatments on Vegetative Growth, Yield and Fruit Quality of “Dessert Red” Peach Trees Grown in Clay Soil

Abstract: This investigation was carried out during 2008 and 2009 seasons to study the effect of three irrigation regimes at 80, 70 and 60% of field capacity (FC) (I1, I2 and I3) and three potassium fertilizer levels at 0.5, 0.75 and 1 kg K2SO4 (48% K2O)/tree (K1, K2 and K3), as well as, their interaction on vegetative growth, nutritional status, water relations, yield and fruit quality in addition to field water use efficiency (FWUE) of "Dessert Red" peach trees budded on Nemaguard rootstock grown in Sedy Salem Distric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 8 publications
29
6
0
Order By: Relevance
“…The reduction in fruit firmness might be due to increasing fruit volume and reducing calcium concentration as influenced by irrigation and fertilizers application. These results coincided with those obtained by Mikhael et al (2010) who reported that deficit irrigation regime induced significantly higher fruit firmness. Furthermore, Salama et al (2012) concluded that the values of fruit firmness of Sewy date fruit were increased when 100% of nitrogen was applied completely via organic form compared to added 100% mineral nitrogen fertilizer.…”
Section: B Fruit Firmnesssupporting
confidence: 92%
See 2 more Smart Citations
“…The reduction in fruit firmness might be due to increasing fruit volume and reducing calcium concentration as influenced by irrigation and fertilizers application. These results coincided with those obtained by Mikhael et al (2010) who reported that deficit irrigation regime induced significantly higher fruit firmness. Furthermore, Salama et al (2012) concluded that the values of fruit firmness of Sewy date fruit were increased when 100% of nitrogen was applied completely via organic form compared to added 100% mineral nitrogen fertilizer.…”
Section: B Fruit Firmnesssupporting
confidence: 92%
“…These findings might be due to advance fruit maturity under drought condition. These results are in accordance with those of Mikhael et al (2010) who found that the values of soluble solids content (SSC) in fruits of "Dessert Red" peach trees increase by decreasing the level of irrigation regime from 80% to 60% field capacity (FC). Other wise, Kaya et al (2010) noticed that there were no significant differences for the tested irrigation regimes in total soluble content of apricot fruit.…”
Section: B Fruit Firmnesssupporting
confidence: 92%
See 1 more Smart Citation
“…Also, the increase of CU under (I 0 ), comparing with (scheduling treatments) might be attributed to increasing the amount of water applied under the conditions of this treatment and hence, the increasing rate of evaporation from the soil surface and transpiration from plant surfaces which resulted from increasing the values of CU. These results are in a great harmony with those obtained by Mikhael et al, (2010) who concluded that, the amount of irrigation water applied for (Desert Red) peach trees were clearly affected by irrigation treatments, where the highest values were recorded under irrigation at 80% of field capacity in comparison with other irrigation treatments 70 and 60% of field capacity. The data in a column followed by the same symbol are not significant at p= 0.05…”
Section: -Influence Of Irrigation Scheduling Treatments Andsupporting
confidence: 89%
“…These results are in full agreement with reported by Ali et al, (1998), and Khalil et al, (2000), who stated that adequate water supply for apple trees in an important factor for maximizing its production. Also, these results agreement with reported by El-Seginy (2006) on "canino" apricot trees and Mikhael et al, (2010) on peach trees.…”
Section: Yieldsupporting
confidence: 92%